Agricultural Policy Reform and Its Impact on Farm Households Income Inequality - Mishra, Ashok K; El-Osta, Hisham; Shaik, Saleem (Journal of Income Distribution®, 2009)
In the United States the 1996 agricultural policy reform ushered in market-oriented farm policies and also gave farmers a seven-year lump-sum payment that was not tied to production. Some scholars argue that farm program payments have changed the distribution of income among farm households. Our study uses a national farmlevel survey for 1996-2001 to investigate a) the distribution of income among farm households, b) the sources that contribute to income inequality, and c) the role of farm program payments in equalizing income. Results show a high but declining income inequality between 1996 and 2001. Among the income components that contributed the most to income inequality was an income component labeled Income from farming and all other sources. Findings further show that marginal increases in both off-farm labor income and farm program payments reduce income inequality. The impact of various income components on overall reduction in income inequality therefore depends on a household’s participation in off-farm work and government farm programs.